IDEOLOGI GERAKAN MUHAMMADIYAH - Erwin Wirawan; Harry; Nurul Imana; Devi Azra Yunus; Asri; Dahlan Lama Bawa (STKIP Subang, 2025)
This article examines the ideology of the Muhammadiyah movement as the foundational framework that shapes its da’wah orientation and socio-religious activism in Indonesia. The study addresses the problem of how Muhammadiyah’s ideological principles function not only as normative religious doctrines but also as operational guidelines that sustain the movement’s relevance amid social change. The research aims to analyze the construction and role of Muhammadiyah’s ideology in guiding organizational consistency, social engagement, and modernization efforts. This study employs a qualitative approach using a library research method. Data were collected from primary sources such as official Muhammadiyah documents and authoritative works of Muhammadiyah thinkers, as well as secondary sources including academic books and peer-reviewed journal articles on Islamic movements and ideology. Data analysis was conducted through qualitative content analysis by identifying key concepts, interpreting their meanings, and examining their interrelationships within the ideological framework. The findings show that the ideology of the Muhammadiyah movement is integrative in nature, combining theological foundations, rational reasoning, and social praxis. The principles of tawhid, amar ma‘ruf nahi munkar, and tajdid function as a coherent value system that guides Muhammadiyah’s educational, health, and social service initiatives. This ideology enables Muhammadiyah to maintain organizational consistency while remaining adaptive to modern social dynamics. The study concludes that ideological consistency plays a crucial role in sustaining Muhammadiyah as a modern Islamic movement oriented toward social progress and the welfare of society.